Supply Chain Financing for Supporting the Children with Special Needs: Problem-Solving Strategies - Venera Sabirova; Baktygul Ðbdymomunova; Kristina Boriskina; Ilhom Davidov; Ð¢aalay Dzhanibekov; Ðbdykalyi Ðšybyraev; Rustam Mamazakirov; Nurbek Ðœatkarimov; Marat Tatenov; Ð¢aalay Turdiev; Mahabat Ð¢atenova (International Journal of Supply Chain Management, 2018)
The purpose of this work is to investigate the supply chain funding in supporting children with special needs in accordance with an existing supplier management framework. Improving the living conditions of homeless and neglected children, as well as children with disabilities, is one of the priority directions for the social and economic development of the main countries. However, often due to the insufficient level of funding and state support, the functioning of such specialized institutions such as orphanages or colleges is reduced to unacceptable conditions. In this article, the authors conducted a comprehensive study of 7 specialized institutions located in southern Kyrgyzstan. Social and macroeconomic factors have been taken into account such as the level of public finance, the local distribution of funds for the need for children, the financing of the supply chain for the support of children, the level of social protection, the psychological microclimate, and the morbiditysituation. Therefore, inter-ethnic tensions and forced migration of the skilled population influence the fact that many minors cannot get adequate nutrition, quality education is practically provided on the street. In this work, measures are proposed to prevent the abandonment of children, increase the role of institutions engaged in educational work with children, finance the supply chain to support children and seek new, more effective forms of adaptation in modern society.Keywords- Children, supply chain financing, rehabilitation and adaptation institution, education, Characteristics of children.